Least squares problem for linear inequalities with bounds on the variables - Popescu, Elena (Rev. Anal. Numér. Théor. Approx., 2004)
In [2] S.P. Han proposed a method for finding a least-squares solution for systems of linear inequalities. Additional information about the real world problem may take the form of additional inequalities. A common case is when the variables are restricted to lie in certain prescribed intervals. A method for this very important case is the subject of this paper.